PENINGKATAN PRODUKTIVITAS BELAJAR MAHASISWA IAIN SYEKH NURJATI CIREBON MELALUI SPIRIT BANGUN PAGI DAN KUALITAS SHOLAT SUBUH - Moh. Agis Ghoni Chakim; Septi Gumiandari (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This research aims to determine the implications of getting up early and praying at dawn for students' lives to increase learning productivity. The subjects in this research were 16 IAIN students who routinely got up early and prayed morning prayers in congregation at the mosque. The research instrument is observation and in-depth interviews with research subjects. The results of the research show that the quality of waking up early and performing morning prayers has a positive influence on students' daily lives. Then the subjects felt the benefits of getting up early and praying at dawn in daily life, especially in terms of respect for time, health and clarity of thinking. Subjects become more appreciative of time and their ability in time management increases. Students' daily activities become more varied, controlled, and every movement becomes more meaningful because every morning begins with a feeling of comfort in studying and the intention to worship in carrying out daily activities.